Enhanced Screw Fixation in Osteoporotic Proximal Femoral Fracture: Augmentation vs Without Augmentation. Literature Review - Niewczas, Karolina; Brzozowska, Adrianna; Bzoma, Michał; Gugulska, Julia; Bielicka, Anna; Czerepak, Irmina; Komasara, Piotr; Domoń, Dominik; Niedziela, Adam; Kozon, Katarzyna; Bochenek, Hubert (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Osteoporosis is a common cause of proximal femoral fractures, which also are called hip fractures. The incidence of osteoporosis is increasing and becoming widely population disease. The division of proximal femoral fractures is based on anatomy, which includes trochanter, neck and head of femur fractures. There are the most severe osteoporotic fractures with a high mortality and disability. Therefore, decreased thickness in osteoporosis implies mechanical difficulties with treatment. Treatment is dependent on the appropriate scales, related to the anatomical division of hip fractures. It contains appropriate fixation with sliding hip screw with plate or nailing. In other cases, especially in elderly patients with symptomatic hip arthritis, total hip arthroplasty may be considered. Aim of the study: Proximal femoral fractures in osteoporotic patients are not only associated with difficulties in treatment, but more importantly with high mortality and disability. This is why further development of treatments is so important. In the following work, it is shown up-to-date methods of treatment proximal femoral fractures. Furthermore, promising method with enhanced screw fixation with augmentation is shown with particular attention to safety and good functional results. Material and methods: Review of studies available through sources on PubMed, Google Scholar, and the National Library of Medicine. Conclusions: Proximal femoral fractures vary significantly in treatment depending on the division by anatomy. In addition to anatomy, it is important to consider age and co-morbid symptomatic hip arthritis in treatment. The cement augmentation of the proximal femoral nail antirotation increases the implant stability in osteoporotic proximal femoral fractures. Moreover, cement augmentation is safe method of treatment with good fracture healing.